Big fish in small pond or small fish in big pond? An analysis of job mobility - Ana Rute Cardoso (Institute for the Study of Labor (IZA), 2005)
The statement that individuals care for status and for their position within a hierarchy has been subject to sparse economic analysis. I check this assertion by analyzing wages and status within the firm, with status measured as the worker rank in the firm wage hierarchy. More precisely, I focus on worker mobility between jobs, to compare movers and stayers in terms of gains/losses in wage level versus gains/losses in rank position. The following questions are addressed: Upon switching firm, what do workers gain/loose in terms of wage and in terms of rank position? Is there a trade-off between wage and rank? If so, does it vary across groups of workers? A remarkable longitudinal linked employer-employee dataset is used. Estimation takes account of worker unobserved heterogeneity. Results indicate that movers are subject to slower rank progression than stayers. That penalty is larger the larger the new firm when compared to the old one. Moreover, faster rank progression is achieved by movers at the price of slower wage progression, suggesting the existence of a trade-off between wage and status.
Keywords: J63; J31; J41; 330; linked employer-employee data; job mobility; wage structure; wage ranks